2017
DOI: 10.1091/mbc.e17-01-0017
|View full text |Cite
|
Sign up to set email alerts
|

RABL2 interacts with the intraflagellar transport-B complex and CEP19 and participates in ciliary assembly

Abstract: RABL2 interacts with the intraflagellar transport-B (IFT-B) complex and CEP19 in a mutually exclusive manner. A point mutation of RABL2 found in sperm motility–defective mice abolishes its binding to IFT-B but not to CEP19. A RABL2-defective Chlamydomonas strain exhibits a nonflagellated phenotype, suggesting a crucial role of RABL2 in ciliary assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
105
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(116 citation statements)
references
References 47 publications
10
105
1
Order By: Relevance
“…Rabl2 is an atypical Rab small GTPase that promotes anterograde IFT from the ciliary base 26,[32][33][34] . Recently, we have shown that Rabl2 is required for ciliary targeting of Htr6 and Gpr161, with which it interacts 26 .…”
Section: Htr6 Cts1 and Cts2 Contribute To Rabl2 Bindingmentioning
confidence: 99%
“…Rabl2 is an atypical Rab small GTPase that promotes anterograde IFT from the ciliary base 26,[32][33][34] . Recently, we have shown that Rabl2 is required for ciliary targeting of Htr6 and Gpr161, with which it interacts 26 .…”
Section: Htr6 Cts1 and Cts2 Contribute To Rabl2 Bindingmentioning
confidence: 99%
“…In mammalian cilia, IFT27 was shown to be required for exit of the BBSome complex and associated ciliary cargoes (Keady et al, 2012;Eguether et al, 2014). Recently, Rabl2 was identified as a potential third Rab-like member of the IFT complex as it was shown to regulate IFT initiation and to associate with the IFT74/81 sub-complex Kanie et al, 2017;Nishijima et al, 2017). Interestingly, IFT22 and IFT27 also associate with the IFT74/81 subcomplex (Taschner et al, 2014) suggesting that IFT22, IFT27, and Rabl2 may be located within close proximity in the IFT B1 complex.…”
Section: Introductionmentioning
confidence: 99%
“…S5, d=334±38nm (our data); d=372.6±16.4nm 77 ). This 346 observation is supported by recent evidence suggesting that CEP19 forms a functional complex 347 with FOP and CEP350, distal appendage proteins required for an early step of ciliogenesis 77,78,79 . 348…”
Section: The Architecture Of the Basal Foot Revealed By Super-resolutmentioning
confidence: 66%